Employee Productivity as the Mechanism Linking Management Support and Work Environment to Employee Performance - Yuni Syafrida; Muhammad Donal Mon (Celebes Scholar pg, 2026)
This study examines the relationships among management support, work environment, organizational commitment, employee productivity, and employee performance in the manufacturing sector of Batam, Indonesia. Using a quantitative research design, data were collected from 230 employees working in five manufacturing companies and analyzed through Partial Least Squares Structural Equation Modeling. The findings show that management support and work environment have significant positive effects on employee productivity, whereas organizational commitment does not exert a significant effect. Employee productivity, in turn, has a significant positive effect on employee performance. The results further reveal that management support and work environment do not directly influence employee performance but affect it indirectly through employee productivity. Organizational commitment also does not show a significant indirect effect on employee performance through productivity. These findings indicate that employee performance is shaped less by favorable organizational conditions alone than by the extent to which such conditions are translated into productive work behavior. In this sense, employee productivity emerges as the central mechanism through which organizational resources acquire performance relevance.